Potential Land Suitability For Spatial Planning of Wheat Commodity (Triticum Aestivum) In Tanah Datar Regency - Eggy Arya Giofandi; Anissa Zuhrita; Assyaroh Meidini Putriana; Dhanu Sekarjati; Fitrah Andika Riyadhno; Ade Mashuri; Opi Sepriani; Muhammad Rifqi; Triyatno; Ahyuni; Cipta Estri Sekarrin (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2022)
One of hindrances faced by Indonesia agriculture sector is domestic agriculture production that does not cover the market demand such as wheat commodity. The aim of this research is to calculate the spatial planning for wheat commodity in Tanah Datar Regency by using matching calculation with Fuzzy set method to find out the land physical ability. The method used in this research using fuzzy set equations and Boolean approach. The research results obtain land suitability 111.132 ha for suitable category, 20.239 ha for quite suitable, and 137 m2 for unsuitable category. Then after the land suitability is obtained, development instruction is given for the agriculture planning of wheat commodity with Boolean approach. The result of development instruction reaches 42.873 ha spread in all over sub districts with the highest development potency is at North Lintau Buo Sub District 9.657 ha and Lintau Buo Sub District 7.348 ha. This development potency can be used as the initial reference for planting wheat commodity (Triticum aestivum) in Tanah Datar Regency.